Modeling of syngas biomethanation and catabolic route control in mesophilic and thermophilic mixed microbial consortia. (15th March 2020) - Grimalt-Alemany, Antonio; Asimakopoulos, Konstantinos; Skiadas, Ioannis V.; Gavala, Hariklia N.
Highlights: The syngas biomethanation process was successfully modelled for the first time. Thermodynamically-consistent models allowed thermodynamic competition predictions. Thermodynamic limitation on hydrogenogens triggers acetate production. Microbial activity can be directed through catabolic route control. Abstract: The syngas biomethanation process is a promising bioconversion route due to its high versatility, as it could be applied as a stand-alone technology, coupled to gasification plants, and integrated in anaerobic digestion or bioelectrochemical conversion systems. The biomethanation of syngas typically takes place through a rather complex network of interspecies metabolic interactions, which may vary significantly depending on the operating conditions applied and the diversity of microbial groups present. Despite there are several benefits derived from using microbial consortia, these also present challenges associated with limited process control and low product selectivity. To address the latter, the syngas biomethanation process carried out by mesophilic and thermophilic microbial consortia was modelled with the ultimate goal of studying possible catabolic route control strategies through the modulation of key operating parameters. The results showed that the thermophilic microbial consortium presented much higher apparent specific methane productivity (18.8 mmol/g VSS/d) than the mesophilic (4.6 mmol/g VSS/d) at an initial PCO of 0.2 atm, and that the difference increased with increasing initial PCO . This difference in productivity was found to derive from the catabolic routes used rather than the kinetic parameters of each microbial consortium. Additionally, the thermodynamic considerations included in the models revealed the possibility of controlling the catabolic routes used by each consortium through the modulation of the mass transfer and PCO2 . Our results strongly indicate that modulating the PCO2 is a promising operational strategy for boosting the product selectivity towards CH4, the productivity of the system and the biomethane quality simultaneously.